Is micronucleus assay a useful marker in gingiva, tongue, and palate for evaluating cytogenetic damage induced by chemical, physical, and biological agents in vivo? A systematic review with meta-analysis - Pinto, Thiago Guedes (2025)
The present systematic review (SR) aims to evaluate manuscripts in order to help further elucidate the following question: is the micronucleus assay (MA) also a useful marker in gingiva, tongue, and palate for evaluating cytogenetic damage in vivo? A search was performed through the electronic databases PubMed/Medline, Scopus, and Web of Science, all studies published up to December 2023. The comparisons were defined as standardized mean difference (SMD), and 95% confidence intervals (CIs) were established. Full manuscripts from 34 studies were carefully selected and reviewed in this setting. Our results demonstrate that the MA may be a useful biomarker of gingival tissue damage in vivo, and this tissue could be a useful alternative to the buccal mucosa. The meta-analysis analyzing the different sites regardless of the deleterious factor studied, the buccal mucosa (SMD = 0.69, 95% CI, − 0.49 to 1.88, p = 0.25) and gingiva (SMD = 0.31, 95% CI, − 0.11 to 0.72, p = 0.15), showed similar results and different outcome for the tongue (SMD = 1.19, 95% CI, 0.47 to 1.91, p = 0.001). In summary, our conclusion suggests that the MA can be a useful marker for detecting DNA damage in gingiva in vivo and that this tissue could be effective site for smearing.